Can Nitrogen Source and Nitrification Inhibitors Affect In-Season Nitrogen Supply?. Issue 16 (7th September 2020) - Redding, M.R.; Phillips, I.; Pratt, C.; Paungfoo-Lonhienne, C.; Levett, I.; Hill, J.; Mehta, C.; Bailey, T.; Brackin, R.; McAuley, J.; Pratt, S.; Laycock, B.; et al.
ABSTRACT: This study sought to identify whether piggery effluent-derived nitrogen sources can be formulated with urea and nitrification inhibitors to better synchronize nitrogen (N) supply with crop demand than conventional urea fertilizer alone. A 288 pot pasture growth and leaching growth accelerator trial (5 pasture cuts) was completed with a factorial treatment structure of three N sources (2.63 g N [kg soil] −1 applied as 100% urea-N, 8% struvite-N + 92% urea-N, and 8% piggery pond sludge-N + 92% urea-N), five rates of three nitrification inhibitors (including 3, 4-Dimethylpyrazole phosphate, DMPP; limonene+ethanol; and dicyandiamide, DCD), and matrix encapsulated forms of these inhibitors. Applying a combination of piggery sludge with urea increased N uptake during the first 4 weeks of plant growth (by 65%), though total N uptake throughout the trial (22 weeks) did not differ across the N-sources. The microbial community of the soil to which the sludge was added was significantly different from the un-amended soil at the conclusion of the trial. All inhibitor formulations significantly decreased leaching losses of mineral-N relative to the control (by 14 to 61%). The use of DMPP decreased initial nutrient uptake, deferring uptake until later in the experiment. Inhibitor addition resulted in microbial community effects that persisted throughout the trial. The study demonstrated that a piggery-derived N-source and a nitrification inhibitor can be used to manipulate plant N uptake to occur later or earlier in a growing period with equal cumulative uptake, achieving an 11% increase in residual N store, and decreased N leaching losses.